Antara Pancasila dan Kulliyyat Al-Khams: Tinjauan Maqashid Syariah terhadap Keluarga Muslim dalam Bermasyarakat Dan Bernegara - Robitoh Alamhadi Faisal (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the compatibility of Pancasila with maqāṣid al-sharī‘ah from the perspective of uṣūl al-fiqh. In Indonesia, a country with a Muslim majority, not all Muslims recognize or are convinced that Pancasila embodies Islamic values. Some groups argue that Islamic legitimacy can only be achieved if the Qur’an and Sunnah formally serve as the foundation of the state. However, the historical development of Islamic thought demonstrates the emergence of various schools of jurisprudence, theology, and mysticism, reflecting interpretative diversity shaped by socio-cultural and historical contexts. Within Indonesia’s pluralistic national framework, the Qur’an and Sunnah are not adopted as the constitutional basis of the state due to the potential for multiple interpretations, which are relative and may lead to the domination of particular textual readings. This research employs a doctrinal legal method, positioning law as a normative system. It utilizes analytical and case approaches to examine scholarly opinions concerning maqāṣid al-sharī‘ah. The findings reveal that the principles of Pancasila align with al-Kulliyāt al-Khams, the five essential objectives of Islamic law. The protection of religion (ḥifẓ al-dīn) is reflected in the First Principle; the protection of life (ḥifẓ al-nafs) in the Second Principle; the protection of lineage (ḥifẓ al-nasl) in the Third Principle; the protection of intellect (ḥifẓ al-‘aql) in the Fourth Principle; and the protection of property (ḥifẓ al-māl) in the Fifth Principle. Therefore, Pancasila can be understood as representing universal Islamic values within the framework of the Indonesian nation-state.